Morphological changes in human neural cells following tick-borne encephalitis virus infection - Růžek, Daniel; Vancová, Marie; Tesařová, Martina; Ahantarig, Arunee; Kopecký, Jan; Grubhoffer, Libor (The Journal of general virology, 2009)
Tick-borne encephalitis (TBE) is one of the leading and most dangerous human viral neuroinfections in Europe and north-eastern Asia. The clinical manifestations include asymptomatic infections, fevers and debilitating encephalitis that might progress into chronic disease or fatal infection. To understand TBE pathology further in host nervous systems, three human neural cell lines, neuroblastoma, medulloblastoma and glioblastoma, were infected with TBE virus (TBEV). The susceptibility and virus-mediated cytopathic effect, including ultrastructural and apoptotic changes of the cells, were examined. All the neural cell lines tested were susceptible to TBEV infection. Interestingly, the neural cells produced about 100- to 10,000-fold higher virus titres than the conventional cell lines of extraneural origin, indicating the highly susceptible nature of neural cells to TBEV infection. The infection of medulloblastoma and glioblastoma cells was associated with a number of major morphological changes, including proliferation of membranes of the rough endoplasmic reticulum and extensive rearrangement of cytoskeletal structures. The TBEV-infected cells exhibited either necrotic or apoptotic morphological features. We observed ultrastructural apoptotic signs (condensation, margination and fragmentation of chromatin) and other alterations, such as vacuolation of the cytoplasm, dilatation of the endoplasmic reticulum cisternae and shrinkage of cells, accompanied by a high density of the cytoplasm. On the other hand, infected neuroblastoma cells did not exhibit proliferation of membranous structures. The virions were present in both the endoplasmic reticulum and the cytoplasm. Cells were dying preferentially by necrotic mechanisms rather than apoptosis. The neuropathological significance of these observations is discussed.
Keywords: Endoplasmic Reticulum; Cell Line; Cell Death; endoplazmatické retikulum; Cytoskeleton; Encephalitis Viruses, Tick-Borne; buněčná smrt; neurony; virion; Cell Membrane; cytoplazma; lidé; Cytoplasm; Virion; Humans; Neurons; buněčná membrána; cytoskelet; neuroglie; buněčné linie; apoptóza; viry klíšťové encefalitidy; Neuroglia; Apoptosis